2015
DOI: 10.1038/ismej.2015.76
|View full text |Cite
|
Sign up to set email alerts
|

Cross-depth analysis of marine bacterial networks suggests downward propagation of temporal changes

Abstract: Interactions among microbes and stratification across depths are both believed to be important drivers of microbial communities, though little is known about how microbial associations differ between and across depths. We have monitored the free-living microbial community at the San Pedro Ocean Time-series station, monthly, for a decade, at five different depths: 5 m, the deep chlorophyll maximum layer, 150 m, 500 m and 890 m (just above the sea floor). Here, we introduce microbial association networks that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 65 publications
14
98
0
Order By: Relevance
“…There can be substantial variation in diversity and function among individual bacterioplankton taxa at the phyla and class levels coupled with the dispersal capacity and response to environmental stressors of these taxa (see, e.g., Langenheder et al ., ; Comte et al ., ; SzĂ©kely and Langenheder, ). Hence, while previous studies have highlighted the importance of environmental conditions in shaping the composition of entire microbial communities (see, e.g., Sunagawa et al ., ; Cram et al ., ; Salazar et al ., ), we extend these findings by inferring metacommunity assembly mechanisms from a well‐established theoretical framework and also to assess variation at the phyla and class level. Moreover, by applying a metacommunity framework to our analyses, we sought to characterize differential influences of spatial and environmental drivers on the assembly of bacterioplankton assemblages.…”
Section: Resultsmentioning
confidence: 98%
“…There can be substantial variation in diversity and function among individual bacterioplankton taxa at the phyla and class levels coupled with the dispersal capacity and response to environmental stressors of these taxa (see, e.g., Langenheder et al ., ; Comte et al ., ; SzĂ©kely and Langenheder, ). Hence, while previous studies have highlighted the importance of environmental conditions in shaping the composition of entire microbial communities (see, e.g., Sunagawa et al ., ; Cram et al ., ; Salazar et al ., ), we extend these findings by inferring metacommunity assembly mechanisms from a well‐established theoretical framework and also to assess variation at the phyla and class level. Moreover, by applying a metacommunity framework to our analyses, we sought to characterize differential influences of spatial and environmental drivers on the assembly of bacterioplankton assemblages.…”
Section: Resultsmentioning
confidence: 98%
“…Under the assumption that cohesion measures biotic interactions (Herren and McMahon, 2017), our results support the hypothesis that biotic interactions are stabilizing to microbial community composition. Several recent studies have concluded that biotic interactions can be strong drivers of microbial population dynamics, on par with or exceeding the influence of environmental factors (Cram et al, 2015b;Cabello et al, 2016;Trivedi et al, 2017). For example, many marine bacterial taxa are more strongly related to other bacterial taxa than to habitat variables (Cram et al, 2015b).…”
Section: Ecological Interpretation Of Connectivity and Compositional mentioning
confidence: 99%
“…Due to advances in high‐throughput sequencing technologies, the increased availability of sequence data across large spatio‐temporal scales has provided an opportunity to address this gap in fundamental knowledge in microbial ecology. Recent studies have used co‐occurrence network analysis as a tool to decipher the potential intraspecies or interspecies interactions in the complex microbial assemblages in oceans (Cram et al ., ), lakes (Eiler et al ., ; Kara et al ., ) and soils (Barberan et al ., ; Berry and Widder, ; Ma et al ., ) as well as in anthropogenic environments such as activated sludge (Ju et al ., ), anaerobic digesters (Rui et al ., ) and the human gut (Faust et al ., ). These findings revealed that microbial communities generally have nonrandom co‐occurrence patterns and modular structures, which strongly implies the essential role of biotic interactions in governing community assembly and ecosystem function.…”
Section: Introductionmentioning
confidence: 99%